Handbook of research on promoting business process improvement through inventory control techniques - Shah, Nita H.; Mittal, Mandeep, 1978- (Business Science Reference, 2018)
"This book explores the various methods for inventory control and management using optimization techniques, data mining concepts and genetic algorithms. It explores how inventory control and management is very tedious job faced by all organizations in any sector of the economy"--Resumé vydavatele
Keywords: logistika (management); řízení zásob; business logistics; inventory control; příručky; elektronické knihy; handbooks and manuals; electronic books